Factors Affecting Selection of Multiplexes: An Empirical Study of Consumer Insights - Tarun Kushwaha AND Rishi Dubey (Abhigyan, 2013)
India is a film loving nation. Past researches have helped in identifying the key factors which drive the viewers to watch particular movies. However, with the growth of multiplexes in several cities, venue could also be an influencing factor in the market demand for movies. Multiplexes provide an attractive environment which enhances and intensifies the experience of watching movies. They also offer plenty of support services in addition to core service of screening movies. No work has been reported yet which explains the criterion on which theconsumers select the multiplexes. This study is a maiden attempt in this direction. This is analogous to customer choices of retail stores for shopping.